2004
DOI: 10.1002/ajh.20000
|View full text |Cite
|
Sign up to set email alerts
|

Paucity of TEL‐AML 1 translocation, by multiplex RT‐PCR, in B‐lineage acute lymphoblastic leukemia (ALL) in Indian patients

Abstract: A total of 69 patients of B lineage ALL, 35 children (32 males, 3 females) and 34 young adults (27 males, 7 females) were studied by multiplex RT-PCR to determine the relative frequency of t(9;22), t(12;21), t(1;19), and t(4;11,). Translocation (9;22) was seen in 1/35 (2.8%) and t(1;19) in 2/35 (5.7%) children. None of the children showed t(12;21) and t(4;11) translocations. In young adults, t(9;22) and t(1;19) were seen in 5/34 (14.7%) and 2/34 (5.8%) patients, respectively. None of the latter showed t(12;21)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 11 publications
3
22
1
Order By: Relevance
“…The 2 MLL-AF4-positive pediatric cases in the study were infants aged 7 and 9 months, respectively. This relatively low incidence and paucity of theE2A-PBX and MLL-AF4 transcripts in ALL cases is in accordance with results of earlier studies from our subcontinent [8,9]. The present pilot study is a prospective study that highlights the relative frequencies of the various common chimeric fusion transcripts in B-ALL cases in the Northern Indian population.…”
Section: Introductionsupporting
confidence: 77%
“…The 2 MLL-AF4-positive pediatric cases in the study were infants aged 7 and 9 months, respectively. This relatively low incidence and paucity of theE2A-PBX and MLL-AF4 transcripts in ALL cases is in accordance with results of earlier studies from our subcontinent [8,9]. The present pilot study is a prospective study that highlights the relative frequencies of the various common chimeric fusion transcripts in B-ALL cases in the Northern Indian population.…”
Section: Introductionsupporting
confidence: 77%
“…The frequency of BCR-ABL positivity in adults was 10/44 (22.7 %) and in pediatrics, 5/76 (6.5 %). This is in accordance with most of the studies reported from our subcontinent as well as few studies from the West [4][5][6][7][8][9][10][11][12]. Clinico-hematological features associated with BCR-ABL-positive ALL include high WBC count, older age, male predominance, and FAB L2 blast morphology.…”
Section: Discussionsupporting
confidence: 79%
“…Kantarjian et al [17] found the p190 type of breakpoint in 12 out of 24 adult ALL patients and the p210 in 11 patients, which is quiet comparable to the frequency noted in our study. In a study by Li Hui-yu et al [7], BCR-ABL positivity in ALL was 31.5 %, and all of their nine positive cases had p210 transcript.…”
Section: Discussionmentioning
confidence: 93%
“…5,[21][22][23][24]. Initially, studies reported favorable outcome of t(12;21)-positive ALL patients compared with t(12;21)-negative ALL patients.…”
Section: Imaging Diagnosis Prognosismentioning
confidence: 99%